Regards de jeunes sur leur orientation scolaire : une analyse de l'agentivité de fin de collège d'élèves primo-migrants en France - Maïtena Armagnague; Audrey Boulin (Les éditions de la Maison des sciences de l'Homme, 2023)
This article focuses on the experiences of newly arrived immigrant pupils about their post-secondary orientation in France. It offers an analysis of the main logics of their agentivity. Based on individual and group interviews conducted at the end of secondary school in two Educational Units for Allophone Pupils (UPE2A), we will show that even if their agentivity is partly framed by the school and dependent on their academic skills, there is not systematically a strict correspondence between these manifest academic dispositions and their subjective appropriation. We will point out that the agentivity of these young people is based on other objective and subjective resources which are external to the school. It could help them to appropriate their school career in a distanced manner.